The Effectiveness of Using the Two Stay Two Stray Type Cooperative Model in Learning to Write Negotiation Text - Nurhasani Cantika Dewi (JLER (Journal of Language Education Research), 2024)
The basis of the research background is based on the curiosity of how this type of two stay two stay cooperative model is used in text-based learning, especially in negotiating text material in class X. So that it produces a problem formulation, namely whether the two stay two stray type of cooperative model in text learning is this negotiation effective? This study intends to determine the effectiveness of the two-stay two-stray cooperative model. In this study using an experimental method with a one-group pretest-posttest design. A total of 25 students from class X MIPA 5 were sampled in the study. From the results of the study, it was proven that the initial test and final test showed an increase with an average initial test of 56.36 and an average of 67.6 in the final test. So that, it can be concluded that the two stay two stray type of cooperative model is effectively used in learning to write negotiating texts.